The "goodness" of homemade yogurt: self-provisioning as sustainable food practices in post-socialist Bulgaria. Issue 11 (2nd November 2018) - Yotova, Maria
ABSTRACT: This paper examines self-provisioning and homemade food practices as examples of socially inclusive forms of sustainability that have potential to contribute to the principles of food justice. While homemade food practices in Bulgaria resemble the philosophies of transnational alternative food movements such as Slow Food and the organics, these should not be viewed as a purposeful challenge to increasingly industrialised globalised markets. Rather, I suggest that homemade food in Bulgaria is an alternative to alternative food through its "quiet opposition" to neoliberal policies and post-socialist reforms, perceived as unjust by the majority of Bulgarian citizens. Moral support for elderly people and village dwellers, suffering most from discriminatory policies, growing economic inequalities and widening food gaps, is expressed through preferences for the natural taste of homemade foods circulated through informal networks. Whilst the transformative potential of self-provisioning practices as more democratic and socially inclusive forms of sustainability exists, however, it is also important to address the most serious threats to achieving food justice in Bulgaria: growing polarisation between villagers and urban-based policy makers, lack of recognition and stimuli for subsistence farming, and deprivation of access to space and resources for farming and food growing. Through an empirical focus on yogurt this paper demonstrates that food justice issues in Bulgaria do not just relate to the food sustainability in terms of human rights, "fairer" relations of production, environmental conservation and animal well-being, but also to the sustainability of families, communities, national traditions and identities.